Perceptions of Working Mothers Toward Breastfeeding Self-Efficacy - Sylvia Dwi Wahyuni; Budi Santoso; Mira Triharini; Novri Susan (Jurnal Ners, 2020)
Introduction: The benefits of exclusive breast feeding are well-documented; however, in Indonesia, breast feeding rates fall well below global recommendations. One of the factors contributing to the low breast-feeding rates is the economic need for many mothers to work and workplaces not providing an adequate environment in which to do so. The aim of the research was to explore the meaning of breastfeeding self-efficacy from the working mothers’ perspective.Methods: The methodology is phenomenology; hence, it is qualitative in nature. The study was conducted in an outpatient’s department in a hospital in Surabaya, Indonesia. Participants: 8 working mothers working outside the home 40 hours a week, attend lactation class, Indonesian, children ages 7 months to 2 years, and baby born healthy.Results: There were six main themes identified in the women’s stories that related to self-efficacy and breastfeeding: 1) the source of breastfeeding self-efficacy, 2) the benefits of breastfeeding, 3) another woman's experience, 4) perception of workplace control,   5) estimated ability of self-confidence, and 6) decision of breastfeeding. The participants who decided to breastfeed for at least two years tended to think positively about breastfeeding.Conclusion: The women had realistic expectations of the commitment that breastfeeding entailed even though they were faced with many workplace obstacles.